Investigation of curing kinetics of a carbon fiber/epoxy prepreg used in aviation applications - Aydin, Ebru; Hazar Yoruc, Afife Binnaz; Kayaalp, Ayse (WALTER DE GRUYTER GMBH, 2025)
This study investigates the cure kinetics characteristics of a carbon fiber/epoxy prepreg used in the aerospace industry. Understanding the curing behavior of prepreg during the autoclave process is critical for optimizing high-performance composite manufacturing. DSC data obtained at different heating rates (2, 4 and 10 degrees C min-1) were analyzed to provide a comprehensive kinetic profile by determining the enthalpy and exothermic peak temperature for experimental model. Additionally, based on the T-beta extrapolation curve, the optimum cure temperatures; Ti (gel), Tp (cure) and Tf (post) were calculated 139.42, 196.32 and 256.35 degrees C, respectively. Kinetic parameters for kinetic model, including activation energy E a , pre-exponential factor A and reaction order n were calculated by Kissinger, Ozawa and Crane methods. These were integrated into the nth-order reaction model, a model-fitting approach, to derive the kinetic equation for the prepreg and to analyze the relationship between the degree of cure and temperature based on the kinetic model. Consequently, the suitability of the nth-order reaction model was evaluated by comparing it with the experimental model to determine the suitable heating rate and curing temperature range. This study presents a practical example of the autoclave curing mechanism and behavior of carbon fiber/epoxy prepreg used in unmanned aerial vehicle manufacturing.
Keywords: carbon fiber/epoxy; composites; curing kinetics; differential scanning calorimetry; prepreg; nth-order reaction model; CURE KINETICS; RESIN; MECHANISM; FAILURE; STRESS; Materials Science